(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The history of the Kazakh people is of considerable interest. There is no doubt that it is being acquired in Kazakhstan highly relevant, as evidenced by the results of significant scientific research. The author believes that the deployment of a coincidence of historical processes of formation of the Kazakh people and its state – the Kazakh Khanate represents a unique event and a unique inexhaustible significance as naunye problems. This article deals with ethnic and political aspects of the formation of the Kazakh nation, its constituent components, the author focuses on the succession of the various stages of ethno-genetic processes on the territory of modern Kazakhstan. Key words: Ethnicity, ethnogenesis, anthropogenesis, tribe, people, nation, the Kazakh Khanate, the Kazakh people, consolidation.